Penurunan Konsentrasi BOD5, COD dan Padatan Tersuspensi pada Air Limbah dengan Menggunakan Teknologi Lahan Basah Buatan (Constructed Wetland) - De Rozari, Philiphi; Ledoh, Sherlly M.F (Al-Kimia, 2018)
Constructed wetlands are a promising solution technology to effectively treat domestic wastewater in developing countries at low cost. This paper reports the findings of the effectiveness of sand planted with Thypa latifolia with variation of the length of outflow measured from the bottom of the media in removing BOD5, COD, and suspended solids. The experimental design consisted of 12 vertical flow (VF) mesocosms. There were 3 treatments and one control based on the with variation of the length of outflow measured from the bottom of the media (7, 14, and 21 cm). During the five months, the mesocosms were loaded with syntethic wastewater. The influent had a 2-day hydraulic retention time. Samples were monitored for BOD5, COD and TSS. The results showed the concetration of BOD5, COD and TSS reduced significantly after the wastewater were treated with constructed wetland systems. The trend showed that the constructed wetland systems planted with Thypa latifolia had a better performance in comparison with the control. There were no significant differences of BOD5 COD, and suspended solidoutflow among 7, 14 and 21 of constructed wetland systems. This indicated that the length of outflow measured from the bottom of the media did not influence the performance of constructed wetland systems in removing BOD5, COD and TSS